The world sport science training workbook level 2 (Peak Performance, 2005)
In 2003 The World Sports Science Training Workbook was launched to fill a crucial gap in the provision of training advice for athletes and sports people. Now, a year later the book has done far better than I ever imagined. It has sold so many copies it has become the most popular workbook in its field and is being used in the training of many up-and-coming young stars. - The World Sports Science Training Workbook Level 2, takes the concept to the next level so as to move the reader up to competition level in their chosen activity as quickly and efficiently as possible. Ideally, the two books should be used together. The first to set up your basic understanding of the many components related to training, and then the second volume will show how to lift your performance to its ultimate competitive level.